The right to work and rights in the workplace: securing the socio-economic rights of foreign migrant workers in the construction sector in Cape Town - Lorgat, Aisha (Department of Sociology, 2025)
Human rights claims are primarily directed at the state, which is seen as holding the perfect obligation to ensure the realisation of rights, however, other actors who hold imperfect obligations may be more directly responsible for helping rights claimants realise their rights entitlements. This is apparent when it comes to migrants, specifically cross-border migrants, who I argue are especially vulnerable or precarious because of their migrant status and lack of access to citizenship rights. Migration is a contentious issue in much of the world and South Africa is no exception. Migrants form part of the precariat in the host society and are exposed to a range of insecurities that can be tied to and aggravated by their migrant status. They are understood to be denizens (Standing, 2011) who lack citizenship and, as such, their entitlement to some or all rights is denied or at least, called into question. They are also workers who nevertheless do not have a recognised right to work, and should they manage to access employment despite this, their entitlement to workplace rights is frequently undermined if not outright denied. My main question therefore asks how migrants negotiate their lived reality with regard to access to work and rights in their workplaces in South Africa, and what role organisations with indirect rights obligations, such as trade unions and NGOs play in these negotiations. What implications does this have for trade unions as the recognised representatives of workers in South Africa? The research that contributed to this dissertation took place in three separate but related projects, beginning with the African Diaspora project, followed by research conducted specifically for this dissertation and, lastly, research aimed at developing a labour migration policy for Cosatu. The research methodology applied was principally the extended case method along with Orunmila epistemology to help make sense of the data. My research shows that while trade unions have an obligation to help migrants realise their rights to work and rights in the workplace, they face challenges in meeting this obligation. As a result, migrants rely more on themselves and other organisational forms to try to realise these rights. Nevertheless, continued failure of unions in this regard is untenable and reflective of a broader failure to adequately represent precarious workers, a failure that will result in continuing decline for trade unions if they are unable to rise to the challenge.